Screening of psychiatric disorders in women with high‐risk pregnancy: Accuracy of three psychological tools. Issue 2 (18th February 2022) - Hamidia, Angela; Kheirkhah, Farzan; Chehrazi, Mohammad; Basirat, Zahra; Ghadimi, Reza; Barat, Shahnaz; Cuijpers, Pim; O'Connor, Elizabeth; Mirtabar, Seyyedeh Mahboubeh; Faramarzi, Mahbobeh
Abstract: Purpose: This study investigated the optimal cutoff points of three psychological tools for screening psychiatric disorders in women with high‐risk pregnancy. Design and Methods: In this cross‐sectional study (N = 155), s ensitivity/specificity of the Edinburgh Postnatal Depression Scale (EPDS), the Brief Symptom Inventory 53‐items (BSI‐53), and the BSI‐18 were computed with respect to having a psychiatric diagnosis based on the clinical interview. Results: The usual cutoffs (≥13 for EPDS, T‐score of 63 for BSI‐53) demonstrated poor diagnostic accuracy. The optimal thresholds were computed for EPDS cutoff of 6.5, GSI = 0.47 for BSI‐53, and GSI = 0.5 for BSI‐18. Practice Implications: The use of psychological tools among pregnant women with high‐risk pregnancy may need to be modified in order to accurately identify psychiatric disorders.